Mental Illness and Nullity of Marriage: Indian Perspective - Nambi, Siva (Indian J Psychol Med, 2015)
Marriage is a social institution that formalizes and stabilizes the union between a man and wife. At times, either of the parties undergoing the contract of marriage may ask it be declared null and void. Psychiatrists and legal experts may be called in to provide opinion whether such a marriage should be annulled. Some laws in India do state unsoundness of mind as a valid reason for nullity of marriage. However, determining unsoundness of mind can be a difficult issue, especially when made in retrospect. This paper highlights some cases where nullity of marriage was contested in view of unsoundness of mind. Furthermore, some issues encountered by psychiatrists pertaining to nullity of marriage are discussed. Though psychiatrists and legal experts may have different ways of approaching the issue of nullity on the basis of psychiatric disorder, the overall aim of both remains the same of avoiding broken homes, upholding the dignity of the individual and legal framework.